(untitled) (Journal of Engineering, 2016)
This work is concerned with the study of the effect of cement types, particularly OPC and SRPC, which are the main cement types manufactured in Iraq. In addition, study the effect of mineral admixtures, which are HRM and SF on the resistance of high performance concrete (HPC) to internal sulphate attack. The HRM is used at (10%) and SF is used at (8 and 10)% as a partial replacement by weight of cement for both types. The percentages of sulphate investigated are (1,2 and 3)% by adding natural gypsum as a partial replacement by weight of fine aggregate. The tests carried out in this work are: compressive strength, flexural strength, ultrasonic pulse velocity, and density at the age of 7, 28, 90 and 120 days. The results indicated that the SRPC mixes showed lower reduction in the properties of concrete compared to OPC mixes at all ages of test. The greatest reduction in compressive strength was at the age of (90) days for OPC mixes and the age of (28) days for SRPC mixes. After that, the concrete showed the lower reduction for all percentages of sulphate in fine aggregate. The results also indicated that the performance of HRM showed better results than the SF, and the replacement of 10% SF exhibits better results than 8% SF for both types of cement.